Integration of Healthcare Clowns into Pediatric Palliative Care: A Bridge Between Life and Death - Victoria Valdebenito Mac Farlane (International Journal of Integrated Care, 2022)
Introduction: The objective of this paper was to describe the vision of death from the perspective of families of children who experienced palliative care, and team members working in one unit, and to explore the roles of healthcare clowns in working with life and death. The major research of which this paper is part was a requirement of one healthcare clown organization, that since 2008 works as members of the palliative care unit in a public hospital in Chile. Description: Using a qualitative methodology, and an emergent and descriptive design, 26 people, including mothers and team members of one palliative care unit, participated in in-depth interviews and discussion groups separately. Data analysis was performed using grounded theory and critical discourse analysis techniques. Results: The roles played by healthcare clowns in palliative care were accompanying, mediating between team members and families, facilitating to process death, provision of humane care using socioemotional competences, promotion of social relationships, and being complementary therapy. Conclusion: The six roles of healthcare clowns identified by this research have implications for public policies and actions in palliative care. There is also a need to expand this type of work to other public health services in Chile.